Hydrogenotrophic Methanogenesis Under Alkaline Conditions - Wormald, Richard M.; Rout, Simon P.; Mayes, William; Gomes, Helena; Humphreys, Paul N. (Frontiers in Microbiology, 2020)
A cement based geological disposal facility (GDF) is one potential option for the disposal of intermediate level radioactive wastes. The presence of both organic and metallic materials within a GDF provides the opportunity for both acetoclastic and hydrogenotrophic methanogenesis. However, for these processes to proceed they need to adapt to the alkaline environment generated by the cementitious materials employed in backfilling and construction. Within the present study a range of alkaline and neutral pH sediments were investigated to determine the upper pH limit and the preferred route of methane generation. In all cases the acetoclastic route did not proceed above pH 9.0 and the hydrogenotrophic route dominated methane generation under alkaline conditions. In some alkaline sediments acetate metabolism was coupled to hydrogenotrophic methanogenesis via syntrophic acetate oxidation, which was confirmed through inhibition studies employing fluoromethane. The absence of acetoclastic methanogenesis at alkaline pH values (>pH 9.0) is attributed to the dominance of the acetate anion over the uncharged, undissociated acid. Under these conditions acetoclastic methanogens require an active transport system to access their substrate. The data indicates that hydrogenotrophic methanogenesis is the dominant methanogenic pathway under alkaline conditions (>pH 9.0).